Emredici anayasal süre kanunla değiştirilebilir mi? (1982 anayasası m. 106/2 ve cumhurbaşkanı seçimi kanunu m. 3/5) - SEZER, ABDULLAH (My University, 2021)
1982 Anayasası’nda, Cumhurbaşkanlığı makamının boşalması halinde, genel seçime kadar kalan süreye göre bir ayrım yapılmıştır. Bu bağlamda, genel seçime bir yıl veya daha az kalmışsa Türkiye Büyük Millet Meclisi (TBMM) seçimi de Cumhurbaşkanı seçimi ile birlikte yenilenir. Buna karşın genel seçime bir yıldan fazla kalmışsa yalnızca Cumhurbaşkanı seçimi yapılır. Bu takdirde seçilen Cumhurbaşkanı TBMM seçim tarihine kadar görevine devam eder. Anayasa’ya göre her iki hâlde de seçim 45 günde yapılır: “Cumhurbaşkanlığı makamının herhangi bir nedenle boşalması halinde, kırkbeş gün içinde Cumhurbaşkanı seçimi yapılır” (1982 Anayasası, m. 106/2, c. 1). Bu süre 2018’de 7140 no.lu Kanunla 60 gün olarak değiştirilmiştir. Ancak bu kanun Anayasa’ya aykırıdır. Çünkü Anayasa’daki söz konusu süre, kesin ve emredici olup kanunla değiştirilemez.

In case the office of the President of the Republic falls vacant, in terms of the remaining period, a distinstion is made in theConstitution of Turkey 1982. In this context, if the general election is to be held within a year or less, the election of the Grand National Assembly of Turkey (GNAT) shall be renewed together with the election of the President of the Republic. However, if the general election is to be held in over one year, only the Presidential election is renewed. In this case, the President of the Republic newly elected and shall continue to serve until the election date of the GNAT. In accordance with the Constitution of Turkey elections are held in forty five days in both cases:“In case the office of the President of the Republic falls vacant for any reason, the election of the President of the Republic shall be held in forty five days”1 (The Constitution of Turkey 1982, art. 106/2, c. 1). This period was changed to sixty days in 2018 with the law numbered 7140. But this law is unconstitutional. Because, this period in the Constitution is certain and imperative and can not be changed by law
Can the imperative constitutional period be changed by law? (The constitution of Turkey art. 106/2 and the presidential election law art. 3/5)
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Social Sciences and Humanities; Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Social Sciences & Humanities; Anayasa normu; emredici norm; âmir hüküm; Cumhurbaşkanı seçimi; Cumhurbaşkanı yardımcısı; Cumhurbaşkanı Seçimi Kanunu; Constitutional norm; imperative norm; imperative provision; presidential election; Vice-president of the Republic of Turkey; The Presidential Election Law; etc